The HEPD particle detector and the EFD electric field detector for the CSES satellite. (August 2017) - Alfonsi, L.; Ambroglini, F.; Ambrosi, G.; Ammendola, R.; Assante, D.; Badoni, D.; Belyaev, V.A.; Burger, W.J.; Cafagna, A.; Cipollone, P.; Consolini, G.; Conti, L.; et al.
Abstract: The CSES satellite, developed by Chinese (CNSA) and Italian (ASI) space Agencies, will investigate iono-magnetospheric disturbances (induced by seismicity and electromagnetic emissions of tropospheric and anthropogenic origin); will monitor the temporal stability of the inner Van Allen radiation belts and will study the solar-terrestrial coupling by measuring fluxes of cosmic rays and solar energetic particles. In particular the mission aims at confirming the existences (claimed from several analyses) of a temporal correlations between the occurrence of earthquakes and the observation in space of electromagnetic disturbances, plasma fluctiations and anomalous fluxes of high-energy particles precipitating from the inner Van Allen belt. CSES will be launched in the summer of 2017 with a multi-instruments payload able to measure: e.m. fields, charged particles, plasma, TEC, etc. The Italian LIMADOU collaboration will provide the High-Energy Particle Detector (HEPD), designed for detecting electrons (3–200 MeV) and proton (30–300 MeV)), and participates to develop the Electric Field Detector (EFD) conceived for measuring electric field from ∼DC up to 5 MHz. Abstract : Highlights: On Summer 2017, the CSES satellite will be launched to study the near-Earth e.m., plasma & particles environment. The scientific objectives are: litho-atmo-ionosphere coupling, seismic precursors, solar-terrestrial physics & cosmic rays. For CSES, we have built a high-energy particle detector (HEPD) and an electric field detector (EFD). The article introduces the scientific background, the objectives of CSES and the satellite layout. We discuss the features of HEPD and EFD, the calibration procedures and the laboratory tests.